2008
DOI: 10.2337/db08-0450
|View full text |Cite
|
Sign up to set email alerts
|

Correction of HDL Dysfunction in Individuals With Diabetes and the Haptoglobin 2-2 Genotype

Abstract: OBJECTIVE-Pharmacogenomics is a key component of personalized medicine. The Israel Cardiovascular Events Reduction with Vitamin E Study, a prospective placebo-controlled study, recently demonstrated that vitamin E could dramatically reduce CVD in individuals with diabetes and the haptoglobin (Hp) 2-2 genotype (40% of diabetic individuals). However, because of the large number of clinical trials that failed to demonstrate benefit from vitamin E coupled with the lack of a mechanistic explanation for why vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
143
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(150 citation statements)
references
References 41 publications
4
143
2
Order By: Relevance
“…MPO has been associated with increased risk of coronary heart disease [32][33][34] and dysfunctional high-density lipoprotein, also seen with Hp2-2 diabetic patients. 35 This study also documented significant downregulation of anti-inflammatory mediator IL-10 gene and protein, an important molecule in the resolution of inflammation. 36,37 Lower serum IL-10 levels are linked to acute coronary syndromes increasing future atherothrombotic events.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…MPO has been associated with increased risk of coronary heart disease [32][33][34] and dysfunctional high-density lipoprotein, also seen with Hp2-2 diabetic patients. 35 This study also documented significant downregulation of anti-inflammatory mediator IL-10 gene and protein, an important molecule in the resolution of inflammation. 36,37 Lower serum IL-10 levels are linked to acute coronary syndromes increasing future atherothrombotic events.…”
Section: Discussionsupporting
confidence: 53%
“…Hp2-2 genotype may also play a role in high-density lipoprotein function, reducing cholesterol efflux, as previously reported. 35 Finally, the clinical relevance of Hp2-2 genotype in other vascular territories different from peripheral vascular disease is supported by increases in coronary calcification, 39 myocardial infarction, 40 congestive heart failure, and cardiac death. 41 Our results extend these observations by suggesting a potential role for Hp2-2 genotype in the modulation of lower extremity atherosclerosis in the setting of DM.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, vitamin C supplementation increased the oxidative activity of Hb 2-2-hemoglobin bound to HDL and not only increased HDL oxidation but also resulted in a proinflammatory and proatherogenic status [Asleh et al 2008]. …”
Section: Discussionmentioning
confidence: 99%
“…These differences in the antioxidant activity of the Hp 1 and Hp 2 proteins against Hb are dramatically exaggerated when Hb is glycosylated (1), as occurs to a greater extent in DM. Furthermore, despite the greater urgency of clearing the Hp 2-Hb complex in DM due to its increased redox activity, the clearance of the Hp 2-Hb complex by the CD163 receptor is impaired in DM, resulting in a further amplification of oxidative injury that may be mediated by Hb in Hp 2-2 DM individuals (3). We have recently demonstrated that an important target for Hp 2-Hb-mediated oxidation in DM is the high density lipoprotein (HDL) particle.…”
Section: Introductionmentioning
confidence: 99%